Sustainability and Community: An Alliance to Reach Complete Neutrality with Nature - Cossiga, Giovanni Antonio (Advances in Social Sciences Research Journal, 2023)
After the Covid epidemic, the conditions were created for a change in the geopolitical framework. But as Gramsci said “The new one is slow to arrive,” Maybe. But some important innovations on which the changes will be based are there for all to see. The widespread and rapid sentiment regarding global warming among communities globally, even before the serious evolution of the world under stress was announced and disseminated by the press and science. Because communities are forerunners of the sentiment spread by the universal laws that affect matter but also the laws of the human economy and therefore of life itself on the planet. There is nothing new in the fact that the communities were the first to incorporate concern for the planet’s anomalies and that they give prevalence to the theme of the disease of the planet for anthropometric reasons compared to the social issues that usually absorb the debate between the parties. There is therefore a discontinuity between the communities attracted by the danger for future generations and the management of the political parties agitated by the conflict of positions due to the hunger for consensus. Now this hunger for consensus not only does not have a meeting point with the communities but is creating a discontinuity between the unitary tendency of the communities and the contentiousness index of the parties. It could be deduced that we have reached a turning point that puts the problem of the disease of the planet back at the highest point of interests and therefore the unitary tendency of the communities must prevail over the scattering of consensus among the politic parties. As if to say that we must move from the representative democracy of the parties to the direct democracy of the communities. In other words, moving from political governments to technical governments composed of experts and scientists given the growing and decisive importance on the lives of future generations of intervening to correct global warming of the planet.